T63. TOO MUCH OR TOO LITTLE? EXPLORING EFFORT IN SCHIZOPHRENIA WITHIN THE FRAMEWORK OF MOTIVATIONAL INTENSITY THEORY. (18th May 2020) - Décombe, Amandine; Brunel, Lionel; Capdevielle, Delphine; Raffard, Stéphane
Abstract: Background: Motivation impairments have long been seen as a central feature of schizophrenia. Attention has focused on the reward system and effort-based decision-making deficits. However, according to motivational intensity theory (MIT), effort mobilization and perception are not directly – and not only – determined by reward but, fundamentally, by task difficulty. At the same time, the link between effort and difficulty has been poorly studied in schizophrenia. Methods: Therefore, this cross-sectional study compared effort perception in an experimental schizophrenia group with healthy controls. Participants were asked to carry various quantities of objects from one point to another using their hands. Task difficulty was manipulated by increasing the number of objects and the distance covered. Perceived difficulty, perceived effort and walking speed were assessed for all levels of difficulty. Psychotic symptoms, depression, self-efficacy and bodyweight data were also recorded. Results: The results are consistent with MIT, in that perceived effort increased with task difficulty in both groups. Effort and difficulty perceptions were higher in the schizophrenia group, and although this was positively correlated with bodyweight and depression, there was no association with negative symptoms. Importantly, although schizophrenia patients perceived the task as more effortful, walking speed was similar between the two groups, suggesting that the schizophrenia group mobilized more effort to overcome higher perceived effort and difficulty. Discussion: Together, these results suggest that the schizophrenia group perceived the task as more difficult, but mobilized more effort to complete it. This observation could partly explain the chronic decrease in motivation to engage in physically demanding activities, leading to a decline in such activities in daily life among schizophrenia individuals.